A functional comparison of blood and gingival inflammatory polymorphonuclear leucocytes in man. - Wilton, J M (1977)
Polymorphonuclear leucocytes from the human gingival crevice (CREV-PMN) have a defective phagocytic capacity when compared with peripheral blood polymorphonuclear leucocytes (PB-PMN) from the same individual. In a study of fourteen clinically healthy subjects, significantly smaller numbers of CREV-PMN phagocytosed fewer Candida albicans blastospores as compared with PB-PMN. The intracellularkilling capacity of the two cell populations was similar. Removal of specific antibody but not complement significantly depressed blastospore uptake by both cell types. It is postulated that the intrinsic defect of the CREV-PMN is acquired in vivo and may be a general property of PMN from inflammatory sites.